The laboratory study of P441 oil samples separation by using super absorbent polymer from the waste diapers - Prayang Sunny Yulia; Aditya Yoga Pratama; Samsol Samsol; Ridha Husla; Widia Yanti (BIORE Scientia Academy, 2025)
The waste diapers, the second largest waste source after plastic, pose environmental challenges due to their slow degradation of 25-50 years. Reprocessing diaper waste, including utilizing Super Absorbent Polymer (SAP), is crucial. SAP's high absorption capacity aids in research for separating crude oil from water, particularly relevant for Indonesian oil wells with aging infrastructure. Emulsions in crude oil, stabilized by natural chemicals, require demulsification to prevent production issues, underscoring the importance of efficient water-oil separation methods. The research experimentally compares oil-in-water emulsion separation using SAP with and without SAP. The study utilizes waste-based ingredients like used diapers, and tests involve centrifuge processes at varying temperatures. SAP's osmotic properties enable high water absorption, impacting demulsification efficiency. This study investigates the impact of temperature on emulsion separation between water and crude oil. Testing at 26°C and 40°C reveals accelerated separation at higher temperatures due to reduced crude oil viscosity. Waste-containing tubes demonstrate better separation, with SAP absorbing water, enhancing separation efficiency. Increasing centrifuge speed and temperature improve oil-water separation, showcasing SAP's effectiveness in waste management processes. Research findings on crude oil-water separation using diaper waste conclude that demulsification is faster at 40°C due to decreased viscosity; with SAP waste, volumes of water are more efficient at 40°C; SAP's hydrophilic nature traps water in the gel network; SAP enhances separation effectiveness compared to non-SAP methods in saline solutions.